Claiming Neighborhood : New Ways of Understanding Urban Change - Betancur, John Jairo; Smith, Janet L., 1962- (Book collections on Project MUSE., 2016)
"Using historical case studies in Chicago, Betancur and Smith examine the forces shaping neighborhoods today, focusing on both theoretical and practical explanations for why neighborhoods change. A diverse collection of people and institutions, including urban policy experts, elected officials, investors, speculators, academics, service providers, resident leaders, churches, and community-based organizations, compete to control how neighborhoods change and are characterized. Their interactions and power plays ultimately determine the fate of neighborhoods and their residents. A key argument made is that in our postindustrial economy, neighborhoods have become sites of consumption and spaces to be consumed. Discourse is used to add and subtract value from them--for example, a romanticized image of "the neighborhood" too often exaggerates or obscures race and class struggles while celebrating diversity and income mixing. The authors challenge this image, arguing that in order to explain and govern urban space more equitably, scholars and policy makers must reexamine what sustains this image and the power effects produced"--